Hubungan Pendidikan dan Ekonomi:Perspektif Teori dan Empiris - Gatot Subroto (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2014)
This article aimed to examine the relationship and linkages between education and economic based theory of endogenous growth models of Solow and its adaptation. Discussions were associated with various studies that have been conducted both in Indonesia and other countries along with few applied examples. The results showed that the stimulation of investment for education is higher than the physical investment in the long run. Referring to the results, it was concluded that: 1) the causal relationship between the role of education and economic growth becomes more and more evident and stronger; 2) the education sector as a major driver of economic development dynamics encourages long-term process of structural transformation n as the education has a high rate of return in the future. The proportional and appropriate government spending targeted for education programs (universal education) impacted to economic growth. Recommendations for improvement and expansion of equitable access and quality was a must for all citizens. Concretely, citizens’ involvement with the voluntary movement education community was supposed to be extended to immediately realize the ideals of the Indonesian nation as well as a welfare state. ABSTRAKArtikel ini bertujuan untuk mengkaji hubungan dan keterkaitan antara pendidikan dengan ekonomi didasarkan teori model pertumbuhan endogenous Solow dan adaptasinya. Pembahasan dikaitkan dengan berbagai kajian studi yang telah dilakukan baik di Indonesia maupun negara lain dan contoh-contoh terapan. Hasil kajian menunjukkan bahwa investasi bidang pendidikan merupakan stimulasi lebih tinggi dibandingkan dengan investasi fisik dalam jangka panjang. Mengacu hasil kajian dapat disimpulkan: 1) hubungan kausalitas antara peran pendidikan dan pertumbuhan ekonomi menjadi semakin terbukti dan kuat; 2) sektor pendidikan sebagai penggerak utama dinamika perkembangan ekonomi semakin mendorong proses transformasi struktural berjangka panjang, karena pendidikan memberikan high rate of return di masa mendatang. Pengeluaran pemerintah secara proporsional dan tepat sasaran terhadap program pendidikan (rintisan wajib belajar 12 tahun atau pendidikan menengah universal) memberikan dampak percepatan terhadap pertumbuhan ekonomi. Rekomendasi terhadap perbaikan dan perluasan akses secara berkeadilan dan bermutu merupakan keharusan bagi semua warga negara. Secara konkret, keterlibatan masyarakat terhadap gerakan sadar pendidikan hendaknya semakin diperluas agar cita-cita mencerdaskan bangsa Indonesia segera terwujud seiring dengan meningkatnya negara kesejahteraan.